Assessing the outcomes and experiences of care from the perspective of people living with chronic conditions, to support countries in developing people-centred policies and practices: study protocol of the International Survey of People Living with Chronic Conditions (PaRIS survey). Issue 9 (19th September 2022) - de Boer, Dolf; van den Berg, Michael; Ballester, Marta; Bloemeke, Janika; Boerma, Wienke; de Bienassis, Katherine; Groenewegen, Peter; Groene, Oliver; Kendir, Candan; Klazinga, Niek; Porter, Ian; Sunol, Rosa; et al.
Abstract : Introduction: In view of growing populations with chronic conditions, many countries are redesigning their health systems. However, little information is available about how health systems perform from the perspective of people living with chronic conditions. The Organisation for Economic Co-operation and Development (OECD) Member States therefore mandated the OECD to initiate the International Survey of People Living with Chronic Conditions (PaRIS survey), which aims to provide insight in outcomes and experiences of care as reported by people living with chronic conditions. The PaRIS-SUR consortium has been tasked by the OECD to support the development and implementation of the survey. Methods and analysis: As primary care services play a pivotal role in the management of chronic conditions, the PaRIS survey will be implemented in the primary care setting. Data will be collected with a survey among users of primary care services aged 45 years or older, of whom many have chronic conditions. An additional survey is conducted among their primary care providers. The nested study design will allow analysis of the patient-reported data in relation to characteristics of and care provided by primary care providers within and across countries. In 2022, the survey will be tested in a Field Trial in participating countries. Data for cross-country comparison will be collected by the Main Survey in 2023. Ethics and dissemination: Informed consent will be obtained from primary care providers and service users. National Project Managers search ethical approval of the survey in their country, if required. Reporting by the OECD will focus on questions for international comparison. A secured information technology platform will be developed for participants and stakeholders in countries to receive feedback and answer their own questions. Findings will also be disseminated through an international OECD flagship report, conferences, scientific papers and policy briefs, to inform strategies to improve care for people living with chronic conditions throughout the world.